2012
DOI: 10.1097/mbc.0b013e328349cae5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial protein C receptor 1651C/G polymorphism and soluble endothelial protein C receptor levels in women with idiopathic recurrent miscarriage

Abstract: High levels of soluble endothelial protein C receptor (EPCR) induce coagulation dysfunction by inhibiting protein C activation, and activated protein C (APC) activity. We tested whether EPCR 1651C/G promoter variant and changes in plasma soluble EPCR levels are risk factors for idiopathic recurrent spontaneous miscarriage (RSM). A case-control study involving 283 RSM cases and 380 age and BMI-matched control women. EPCR 1651C/G genotyping was performed by PCR-RFLP method. Plasma-soluble EPCR levels were measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…This may be due to excessive placental ECPR shedding or to other pathways leading to maternal vascular endothelial cell stimulation. Studies have also shown that the expression level of sEPCR is related to gene polymorphisms and specific site mutations . In addition, we did not perform in vivo experiments in this study, and we should further validate our findings in vivo using animal models such as mice.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This may be due to excessive placental ECPR shedding or to other pathways leading to maternal vascular endothelial cell stimulation. Studies have also shown that the expression level of sEPCR is related to gene polymorphisms and specific site mutations . In addition, we did not perform in vivo experiments in this study, and we should further validate our findings in vivo using animal models such as mice.…”
Section: Discussionmentioning
confidence: 83%
“…Studies have also shown that the expression level of sEPCR is related to gene polymorphisms and specific site mutations. 53,54 In addition, we did not perform in vivo experiments in this study, and we should further validate our findings in vivo using animal models such as mice.…”
Section: Discussionmentioning
confidence: 95%
“…Variants of inhibitors of the coagulation process may have an association with iRPL. APC activator polymorphisms, such as thrombomodulin gene (THBD) rs1042579 (C1418T) and endothelial protein C receptor gene (EPCR) rs867186 (1652C/G) have been proposed to be risk factors for iRPL due to the association of these variants with lower levels of soluble proteins impeding the adequate regulation of coagulation processes [47,48]. Similarly, the rs2227589 (786G > A) polymorphism in the antithrombin (AT or SERPINC1) gene has been associated with an increased risk of iRPL, as these proteins inhibit the transition of prothrombin to thrombin and avoid the coagulation process [49].…”
Section: Genetic Variants That Affect Hemostasis and Thrombophilia Sumentioning
confidence: 99%
“…Activated PC (aPC) inhibits excessive thrombin generation by limited proteolytic cleavage and inactivation of coagulation factors Va and VIIIa. EPCR gene polymorphisms are associated with recurrent miscarriages and unexplained pregnancy loss ( 12 14 ). Notably, functional deficiency of EPCR is created by its shedding from the membrane surface by the action of metalloproteases ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%